INTEGRASI GAYA MENGAJAR PRACTICE STYLE DAN PHYSICAL LITERACY UNTUK MENINGKATKAN AKTIVITAS FISIK SISWA SEKOLAH DASAR - Syamsul Arifin; Herita Warni; Mashud Mashud; Rian Kurnia (Jurnal Porkes, 2025)
Low physical activity among elementary school children has become a critical public health issue, exacerbated by sedentary lifestyles and rising obesity rates. Conventional physical education is considered ineffective in fostering sustainable active habits. This study aims to analyze the effectiveness of integrating the Practice Style teaching method with the concept of Physical Literacy in increasing students' physical activity. The method used is a quasi-experiment with a pretest-posttest control group design. The sample consisted of 100 third- and fourth-grade students from SD Negeri 5 Sungai Ulin, divided into an experimental group (receiving integrated learning) and a control group (conventional learning). The intervention lasted 8 weeks. Physical activity data were collected using the Physical Activity Questionnaire for Children (PAQ-C) and analyzed using t-tests and effect size calculations. The results showed a very significant increase in the experimental group (average increase of 8.36 points; p < 0.001; Cohen's d = 1.21), while the control group did not experience any significant changes. The conclusion of the study proves that the integration of Practice Style and Physical Literacy is significantly more effective in increasing students' physical activity than the conventional approach.